Effectiveness of Artificially Synthesized Granitic Residual Soil-Supported Nano Zero-Valent Iron (Gr-nZVI) as Effective Heavy Metal Contaminant Adsorbent - Zarime N.?.; Solemon B.; Wan Yaacob W.Z.; Jamil H.; Che Omar R.; Oyekanmi A.A. (MDPI, 2024)
Supported nano zero-valent iron is receiving great attention nowadays due to its effectiveness in treating heavy metal pollutants. Therefore, this study aimed to investigate the effectiveness of granitic residual soil-supported nano zero-valent iron (Gr-nZVI) for the removal of the heavy metals Pb2+, Cu2+, Co2+, Cd2+ Ni2+ and Zn2+ in mixture solutions under different experimental conditions of batch equilibrium tests. In this study, Gr-nZVI was successfully synthesized by using the chemical reduction of Ferric Chloride Hexahydrate (FeCl3.6H2O) and Sodium Borohydride (NaBH4). The physical and chemical properties, morphology and mineralogy of all adsorbents were characterized by the BraeuerEmmettTeller (BET) method, cation exchange capacity (CEC), X-ray fluorescence (XRF), scanning electron microscopy (SEM), field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). Isotherm, kinetic and diffusion model analyses were conducted to fit the experimental data. The results show rapid adsorption within 5 min in the initial adsorption stage for Pb2+ on nZVI (qe.Pb = 17.89 mg/g) and Gr-nZVI (qe.Pb = 15.29 mg/g). nZVI and Gr-nZVI also showed no significant effects on pH and temperature, serving as a good example of an energy-efficient process. The isotherm data fitted better to the Langmuir model and the pseudo-second-order kinetic model for the adsorption of all of the heavy metals. The diffusion models revealed that adsorption was not the only rate-limiting step. In this study, nZVI compared to Gr-nZVI and Gr demonstrated superior adsorption capacity for the heavy metal adsorption selectivity. Hence, these materials can be utilized as alternative energy-efficient adsorbents for the adsorption of metal ions from wastewater. 2023 by the authors.